2019
DOI: 10.1007/978-3-030-19055-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease

Abstract: Kawasaki disease (KD) is an acute and usually self-limiting medium vessel vasculitis of childhood that has a predilection to involve the coronary arteries. It is characterized by the sequential appearance of a constellation of clinical features [1]. However, none of these clinical findings is, in itself, pathognomonic of KD. Many of these clinical features can, in fact, be seen in other common febrile illnesses of children. It is for this reason that the diagnosis of KD is often considered to be a clinical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
(97 reference statements)
1
9
0
1
Order By: Relevance
“…Our ndings were similar to the ndings of Cheraghali F et al [17] introducing skin rash (68.6%) and changes of the lip and oropharyngeal mucosa (60.8%) as the most common manifestations of KD, but were slightly different from Pilania R.K. et al which showed oral cavity and lips' changes as the most common manifestation (> 95%) of KD, and rash as the second (> 90%). Furthermore, our results showed that neck lymphadenopathy was the least common clinical nding which is compatible with Pilania R.K. et al) [18].…”
Section: Discussionsupporting
confidence: 91%
“…Our ndings were similar to the ndings of Cheraghali F et al [17] introducing skin rash (68.6%) and changes of the lip and oropharyngeal mucosa (60.8%) as the most common manifestations of KD, but were slightly different from Pilania R.K. et al which showed oral cavity and lips' changes as the most common manifestation (> 95%) of KD, and rash as the second (> 90%). Furthermore, our results showed that neck lymphadenopathy was the least common clinical nding which is compatible with Pilania R.K. et al) [18].…”
Section: Discussionsupporting
confidence: 91%
“…Besides, the incidence rate of KD in Northeast Asian countries such as Japan, South Korea, and China is 10–30 times more than that in North America and Europe [ 5 ]. For instance, the annual incidence of KD in Japanese children is more than 300 per 100,000 [ 6 ]. During 1997–2002, the incidence rate of KD among Iranian children was 7.4 per 100,000 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, KD has emerged as a major pediatric disorder throughout the developed world (1). In developing countries, KD is currently being diagnosed and reported in both China and India (2)(3)(4). Multiple organs/systems can be involved in KD.…”
Section: Introductionmentioning
confidence: 99%